Globalization and the Post-Creole Imagination : Notes on Fleeing the Plantation - Crichlow, Michaeline A. (Book collections on Project MUSE., 2009)
Globalization and the Post-Creole Imagination" is a major intervention into discussions of Caribbean practices gathered under the rubric of "creolization." Examining sociocultural, political, and economic transformations in the Caribbean, Michaeline A. Crichlow argues that creolization--culture-creating processes usually associated with plantation societies and with subordinate populations remaking dominant groups' cultural forms--must be liberated from and expanded beyond plantations, and even beyond the black Atlantic, to include productions of "culture" in any place where vulnerable populations live in situations of modern power inequalities, from regimes of colonialism to those of neoliberalism. Crichlow theorizes a concept of creolization that speaks to how individuals from historically marginalized groups refashion self, time, and place in multiple ways, from creating art to traveling in search of homes. Grounding her theory in the material realities of Caribbean peoples in the plantation era and the present, Crichlow contends that creolization and Creole subjectivity are constantly in flux, morphing in response to the changing conditions of modernity and creatively expressing a politics of place.